Cooperative Learning, Success for All, and Evidence-based Reform in education - Slavin, Robert E. (Éducation et didactique, 2008)
This article argues that educational practice and policy should be based on evidence from rigorous experiments. Examples of cooperative learning and Success For All are given to illustrate how proven programs have been evaluated and broadly disseminated. Policy initiatives in the U.S. to promote use of proven programs are described. Evidence-based reform is possible in education, but it demands strong research and clear guidance for educators.
Keywords: Educational Policy; Success For All; cooperative learning; evidence-based reform; experiments in education